THE ROLE OF AZERBAIJANI THEATER ACTORS IN THE FORMATION OF UZBEK THEATER ART - Farkhod Adilov; Zaynab Abidova; Umidbek Abdalov; Shikhnazar Rakhimov; Ikhtiyor Salaev (The Bioscan, 2024)
Cooperation between Uzbekistan and the Republic of Azerbaijan has long been widely developed in all fields of science and culture, literature and art. In the development of Uzbek theater art, the creativity and direct support of Azerbaijani theater art workers and dramatists played an important role, as well as the support of artists of other sister republics. Relations between Azerbaijan and Uzbek theater arts developed widely in the late 19th and early 20th centuries.